Model approach for evaluation of school performance - (:unkn) unknown (Computers and Industrial Engineering, 2014)
Student achievement and school performance are heavily affected by different education qualities of schools, diverse education methods in different type of schools, and so forth. In this study, a model for evaluation of school performance is suggested. A standardized national multiple-choice test results were used to specify measurable factors that affects school performance. Effect of these factors on school performance are evaluated qualitatively. Suggested model can be beneficial to studies on continuous evaluation of school performance.
Keywords: Performance evaluation; School performance; Test performance analysis